The potency of edamame (Glycin max (L) Merrill) as high dietary fiber instant pudding - Siregar, Maruli; Arvianti, Made Dinda; Sofyaningsih, Mira (ARGIPA (Arsip Gizi dan Pangan), 2023)
Edamame contains high levels of dietary fiber that has the potential to lower cholesterol levels. This potential can be further developed by processing it into a food product in the form of pudding, which is a popular dessert that has been part of culinary traditions throughout the world for centuries.This study aimed to utilize edamame flour in the manufacture of high-fiber instant pudding that can be well received by the panelists. This study used a Completely Randomized Design (CRD) with the addition of 3 levels of edamame flour (F1 50%, F2 60%, and F3 70%), and control F0 (0%). Organoleptic test using hedonic test and hedonic quality test with 50 consumer panelists. The results of the Kruskal Wallis test showed that the addition of edamame flour in making edamame instant pudding had a significant effect on the level of preference (hedonic) and hedonic quality (p<0.05). The instant pudding formulation selected was F1 with nutritional content per 100 g, namely water content 2.72%, ash 2.03%, protein 13.10%, fat 1.37%, carbohydrates 80.78%, energy 387.85 kcal, energy from fat 12.33 kcal, dietary fiber 40.08%, sodium 0.13%, cholesterol 8.93%, and saturated fatty acids 0.34%. The nutritional content per serving of 5 mg cholesterol, 0 g saturated fat, and 1 g total fat has met the requirements for high fiber claims.